Comparative analysis of three geometric models for crown gear coupling. (June 2019) - Guan, Yabin; Yang, Xiaohui; Fang, Zongde; Chen, Guoding
Highlights: Three generating principles are proposed for hub tooth surface of crown gear coupling. These three finite element mesh models are built, respectively. Loaded tooth contact analysis for crown gear coupling with misalignment is developed. The geometries of these models are compared with each other. Effect of misalignment on contact analysis is discussed for each model. Abstract: Three different generating principles of the hub, which is an important component of crown gear coupling, are proposed to generate the corresponding models in this paper. Model 1 and model 2 use the given geometries that the profile in all planes containing center of the displacement circle is the same as that in the middle section, and that the surface along the rotation axis is generated by a positive continuous modification, respectively. Without given geometries such as model 1 and model 2, model 3 is carried out by simulating the machining process actually formed by a form grinding wheel, and based on meshing theory. Then, finite element models of these three models are built to investigate the load distributions along the hub tooth surface. Finally, the geometry, tooth contact analysis results and load distribution among these models are discussed with an example. The results show that the surface generated by model 1 is the same as that obtained by model 3, but different from that obtained by model 2.